Implementasi Peraturan Menteri Sosial Nomor 11 Tahun 2018 Tentang Penyaluran Bantuan Pangan Non Tunai - Siti, Hotimah; Koesbandrijo, Bambang (Universitas 17 Agustus 1945 Surabaya, 2019)
In the implementation of the distribution of non-cash food assistance (BPNT) in the city of Surabaya, especially in the Sidotopo Kelurahan there are active e-warong and e-warong that are passive (inactive) so that there is a long queue at a certain date and time when the distribution of non-cash food aid (BPNT). In implementing the e-warong program in accordance with Ministry of Social Affairs Republic of Indonesia Regulation Number 11 of 2018 concerning Distribution of Non-Cash Food Assistance (BPNT) according to Van Meter and Van Horn (1975) in Agostino 2006, it provides the view that policy implementation is influenced by six interrelated variables related namely: policy standards and targets / measures and policy objectives, resources, characteristics of implementing organizations, dispositions or attitudes of implementers, communication between related organizations and implementation activities, social, economic and political environment. The purpose of the researcher is to find out and analyze the implementation of the electronic mutual assistance program in Sidotopo Village, Surabaya City. In making thesis using qualitative descriptive methods to describe the phenomena that exist at the time of study. Based on the results of research that has been done, it is known that the standard and policy ratio is not optimal and not yet on target because it only knows in broad outline, resources are the most influential in the implementation of electronic mutual assistance (e-warong) programs, namely the availability of e-warong in Sidotopo Village there is only one, the implementing organization characteristics apply the principles of openness, transparency, and democracy but for e-warong is closed, communication between the implementing organization is only to the implementing TOP so that there is no clarity, harmony and uniformity of information, disposition or attitude of the implementer in this matter lack of knowledge, understanding and depth of policy, response from KPM itself which always accepts and resigns, social, economic and political environmental factors are community strategies to improve economic conditions with the presence of BPNT and e-warong as BPNT suppliers, allegedly there are political conflicts in ith the use of positions with the scope of the family. The author provides recommendations for the implementation of electronic mutual assistance programs (e-warong), especially in the Sidotopo District to be neutral and strict in licensing procurement and the establishment of e-warong, in order to continue to communicate hierarchically, formally and flexibly, preferably there are Standard Operating Procedures that clearly, socialization, education and evaluation must be firm and strict and there is a follow up and in verifying KPM data must be realistic, accurate and reliable. Keywords: Implementation, Non-Cash Food Aid, e-warongIn the implementation of the distribution of non-cash food assistance (BPNT) in the city of Surabaya, especially in the Sidotopo Kelurahan there are active e-warong and e-warong that are passive (inactive) so that there is a long queue at a certain date and time when the distribution of non-cash food aid (BPNT). In implementing the e-warong program in accordance with Ministry of Social Affairs Republic of Indonesia Regulation Number 11 of 2018 concerning Distribution of Non-Cash Food Assistance (BPNT) according to Van Meter and Van Horn (1975) in Agostino 2006, it provides the view that policy implementation is influenced by six interrelated variables related namely: policy standards and targets / measures and policy objectives, resources, characteristics of implementing organizations, dispositions or attitudes of implementers, communication between related organizations and implementation activities, social, economic and political environment. The purpose of the researcher is to find out and analyze the implementation of the electronic mutual assistance program in Sidotopo Village, Surabaya City. In making thesis using qualitative descriptive methods to describe the phenomena that exist at the time of study. Based on the results of research that has been done, it is known that the standard and policy ratio is not optimal and not yet on target because it only knows in broad outline, resources are the most influential in the implementation of electronic mutual assistance (e-warong) programs, namely the availability of e-warong in Sidotopo Village there is only one, the implementing organization characteristics apply the principles of openness, transparency, and democracy but for e-warong is closed, communication between the implementing organization is only to the implementing TOP so that there is no clarity, harmony and uniformity of information, disposition or attitude of the implementer in this matter lack of knowledge, understanding and depth of policy, response from KPM itself which always accepts and resigns, social, economic and political environmental factors are community strategies to improve economic conditions with the presence of BPNT and e-warong as BPNT suppliers, allegedly there are political conflicts in ith the use of positions with the scope of the family. The author provides recommendations for the implementation of electronic mutual assistance programs (e-warong), especially in the Sidotopo District to be neutral and strict in licensing procurement and the establishment of e-warong, in order to continue to communicate hierarchically, formally and flexibly, preferably there are Standard Operating Procedures that clearly, socialization, education and evaluation must be firm and strict and there is a follow up and in verifying KPM data must be realistic, accurate and reliable. Keywords: Implementation, Non-Cash Food Aid, e-warong